Penerapan Pembelajaran Membaca Al-Quran Melalui Media Pembelajaran Bagi Anak Tunagrahita Di Kelas III SLB Insan Mulia Payakumbuh - Anggriani, Sindi; Januari, Januari ; Abdul Karim, Hamdi; Arif, M. (Faidatuna, 2024)
This study applies the application of learning to read the Koran for mentally retarded children in Class III SLB Insan Mulia Payakumbuh. The introduction explains the importance of education in developing children's potential, as well as the role of education in educating the nation's life and creating a quality generation. This study uses a qualitative descriptive approach, with data obtained through observation, interviews and documentation. The results showed that the preparation for the implementation of learning included making learning tools, mastering the material, and preparing media and a conducive environment. Implementation of learning includes conditioning students, praying together, doing apperception, and conveying learning objectives. Supporting factors include the government's good role and community response, while inhibiting factors include a shortage of teachers and adequate facilities. In conclusion, the application of learning to read the Koran for mentally retarded children at SLB Insan Mulia Payakumbuh needs to be properly prepared, paying attention to preparation, implementation, as well as supporting and inhibiting factors that can influence the success of the learning process. It is hoped that the results of this research can contribute to improving the quality of learning for mentally retarded children in SLB.